Electron Beam Crosslinked Polyurethane Shape Memory Polymers with Tunable Mechanical Properties. Issue 11 (7th November 2012) - Hearon, Keith; Nash, Landon D.; Volk, Brent L.; Ware, Taylor; Lewicki, James P.; Voit, Walter E.; Wilson, Thomas S.; Maitland, Duncan J.; Lendlein, Andreas
Abstract Novel electron beam crosslinked polyurethane shape memory polymers with advanced processing capabilities and tunable thermomechanical properties have been synthesized and characterized. We demonstrate the ability to manipulate crosslink density in order to finely tune rubbery modulus, strain capacity, ultimate tensile strength, recovery stress, and glass transition temperature. This objective is accomplished for the first time in a low‐molecular‐weight polymer system through the precise engineering of thermoplastic resin precursors suitable for mass thermoplastic processing. Neurovascular stent prototypes were fabricated by dip‐coating and laser machining to demonstrate processability.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>